Vulpes chama (Carnivora: Canidae). (5th July 2019) - Lavoie, Maxime; Renard, Aurélie; Pitt, Justin A; Larivière, Serge
Abstract: Vulpes chama (Smith, 1833), commonly called the Cape fox, is 1 of 11 species of Vulpes . It is the only species of Vulpes occurring in southern Africa, and is endemic to that region. It occurs in southern Angola, Botswana, Namibia, South Africa, and southwestern Zimbabwe. V. chama is a slender-built fox and its pelage is silvery gray throughout, back of pinna is tawny, and white hairs occur in the front along pinna edge. It tends to occupy arid and semiarid open habitats and feeds mainly on small mammals and insects, but also consumes birds, small reptiles, and fruits. V . chama is not of conservation concern and is listed as "Least Concern" by the International Union for the Conservation of Nature and Natural Resources.